Design and Synthesis of Polyimide Covalent Organic Frameworks - Zhang, Ya; Huang, Zhe; Ruan, Bo; Zhang, Xinke; Jiang, Tao; Ma, Ning; Tsai, Fang‐Chang (Macromolecular rapid communications., 2020)
As a subseries of the covalent organic framework (COF) material family, polyimide‐based covalent organic framework (PI‐COF) material, which has the advantages of high stability of polyimide, high specific surface area, and controllable pores of COF material, is expected to be a new type of porous material with potential applications. Although the development of PI‐COF is in the early stages during the past decade, it has attracted extensive attention and is widely used in heterogeneous catalysis, gas separation, and storage fields. Therefore, this review is aiming to give a comprehensive understanding of the recent progress of PI‐COFs. This article summarizes the progress of PI‐COF from three aspects: controllable structure design, synthesis method, and application. First of all, under the guidance of network chemical design principles, the topology type of PI‐COF and the size and shape of the formed pores are summarized in terms of different organic monomers. Then the five synthetic strategies for the synthesis of PI‐COF are analyzed. Finally, the applications of PI‐COF in adsorption and separation, drug delivery, solar‐to‐electrochemical energy storage, photocatalysis, and electrocatalyst are introduced. Polyimide‐based covalent organic framework (PI‐COFs) materials are a new class of porous materials, which combine the high stability of PI with the high surface area, crystallinity, and adjustable pores of COF. This article reviews the progress of existing PI‐COFs in controllable structure design, synthesis methods, and applications, and prospects for the future development of the material.